Effectiveness of Preventive Health Programs in Mitigating Chronic Diseases: A Meta-Analytical Review - Saeful Amin (Medical Studies and Health Journal (SEHAT), 2024)
This study aims to examine the effectiveness of digital health interventions in improving the scalability and sustainability of preventive health programs for chronic disease prevention. Using meta-analysis methods, this research synthesizes the results of various studies evaluating preventive health programs involving digital technology, and compares them with traditional approaches. Meta-analysis results show that digital health interventions significantly improve program effectiveness in reducing chronic disease risk, with significant contributions to population reach and sustainability of interventions. These findings provide important insights for the development of more inclusive and sustainable preventive health programs, and recommend the adoption of digital technologies in health systems to improve public health outcomes.